The forensic mental health profile of women offenders in the Eastern Cape, South Africa - Nagdee, Mohammed (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Introduction There is a dearth of research on mental health issues in women offenders in South Africa, especially regarding their socio-demographic backgrounds, offence characteristics, and forensic mental health profiles. Objectives This study examined the psychosocial and forensic mental health profile of women offenders referred by eastern Cape courts for forensic evaluation. A range of socio-demographic, criminological, clinical and forensic mental health variables were systematically explored. Methods A bi-phasic, mixed methods study design was adopted. The clinical and forensic records of all women referred for forensic evaluation to Fort England forensic psychiatric hospital in the Eastern Cape, South Africa were retrospectively reviewed, comprising 173 individual cases in the study period of 1993-2017. Inferential statistical analyses (chi-squared and multivariate logistic regression) were applied to explore relationships between variables and offending outcomes of nterest. Detailed semi-structured interviews were subsequently conducted with a sub-sample of 8 women with mental disorder and violent offending ackgrounds. Interview transcripts thematically analysed. Results Most women came from impoverished and disadvantaged backgrounds. Whilst the majority were first offenders, a high proportion had violent index offences, with murder, attempted murder and assault with intent to do grievous bodily harm accounting for over half of cases. The majority of victims of violence were well known to the perpetrator, especially as biological children, intimate male partners or close family members. Biological children in their first year of life were particularly vulnerable to being victims of homicidal violence. Disproportionately high rates of pre-offence mental illness, alcohol misuse, HIV infection and prior abuse of the offender (especially by intimate male partners) were present. High rates of severe mental disorders (especially psychiatric comorbidity and psychotic-spectrum disorders), and relatively low rates of personality disorders and substance disorders were diagnosed. The majority of women were declared to lack trial competence and criminal capacity, respectively, following forensic evaluation. Women who had backgrounds of prior abuse themselves had over three mes the odds of subsequent violent offending in general, and almost six times the odds of homicidal offending in particular. Homicidal offences were significantly more commonly committed by women with no prior psychiatric history and no psychiatric comorbidity. Women who committed homicide had over eleven times of killing children as opposed to adults. Women over the age of 30 years, and those without psychiatric comorbidity, were significantly less likely to have killed children. Thematic analysis of interviews emphasized the important roles played by gender, self-image, and mental health in violent offending pathways. Conclusions A complex array of socio-demographic, criminological, clinical and forensic variables interact in women offenders of the Eastern Cape referred by courts for forensic evaluation. Exploration of these factors improves understanding of the broader psychosocial context of female offending, and of the personal experiences of the women themselves. This in turn provides an enhanced gender-focus to guide the progressive changes required in policy, legislative, clinical and research endeavours in this field.
Keywords: Female offenders -- Mental health; Female offenders -- South Africa -- Psychology; Female offenders -- South Africa -- Mental health; People with mental disabilities and crime; Women murderers -- South Africa; Forensic psychology -- South Africa; Fort England Psychiatric Hospital